Kinetics and Mechanism of Oxidation of Carbenicillin by Copper (III) Periodate Complex in Aqueous Alkaline Medium - Yuv Raj Sahu; Parashuram Mishra (Journal of Chemistry)
Kinetics and mechanism of oxidation of carbenicillin by diperiodatocuprate [DPC-III] in aqueous alkaline medium were studied spectrophotometrically at 298 K and an ionic strength of 0.10 mol·dm−3. The reaction between DPC (III) and carbenicillin in the alkaline medium showed (CRBC : DPC-III) 1 : 4 stoichiometry. The reaction products were identified by the CHNS test, FT-IR, and LC-MS spectral reports. The reaction was of pseudo-first order with respect to DPC (III) and fractional order with respect to carbenicillin as well as alkali but retarding effect with respect to periodate. Monoperiodatocuprate (MPC-III) was found to be the main active species in the alkaline medium in the form of [Cu (H2IO6) (H2O)2]. Activation and thermodynamic parameters with respect to uncatalyzed rate constants (ku) and slow step rate constant (k) as well as equilibrium constants were determined. The plausible mechanism consistent with experimental results was proposed and discussed in detail.